Chiripa technique. Report of a novel technique to protect the spinal cord from incidental durotomies during complex spinal procedures. (January 2019) - Girolami, Marco; Pipola, Valerio; Ghermandi, Riccardo; Tedesco, Giuseppe; Evangelisti, Gisberto; Gasbarrini, Alessandro
Highlights: Incidental durotomy is the most common intraoperative complication reported in spine surgery literature. A technique for circumferential protection to the neurostructures during posterior-only procedures is presented. Chiripa technique is simple and inexpensive in providing a 360° protective coating. Abstract: Background context: Incidental durotomy is the most frequent intraoperative complication reported in spinal literature. Multiple strategies have been suggested to manage it. Methods: A brief technical report. Discussion: The use of cottonoids is a recommended measure to avoid incidental durotomies during spinal surgeries; thus, ventral protection might be difficult to achieve. This "Chiripa technique" provides circumferential protection to the neurostructures, so that surgical procedures can be safely carried out. Conclusion: Taking into account the low costs and ease of execution, this can be a valuable tip that may widely extended in all cases where a circumferential dural protection is needed.